Johannes Valentini Lucubrata opuscula poeticohistorica in unum collecta [Az éjjeli mécs világánál alkotott költői-történeti művecskéim egybegyűjtése] (1808) című kötetének őstörténeti vonatkozásai - Szörényi, László (Antikvitás & Reneszánsz, 2019)
As a poet, the parish priest Johannes Valentini (Turčiansky Michal, 1756 – Kláštor pod Znievom, 1812) is very much tied to the other Neo-Latin priest-poets living in Hungary and the other countries of the Habsburg Empire by the tradition of laudation in occasional poetry, which flourished from the antiquity until the end of the 19th century and was a tool to praise or mourn religious superiors or secular patronising potentates. Valentini, however, is different from the other poets in his very extensive interest in prehistory. When he poeticises the history of the provostry of Thurocz, he engages in lengthy explanations which are far bigger in size than the poem itself, and are also supplemented with footnotes. From a viewpoint of history of science this approach is probably connected mostly to the research initiated by the Jesuit historian Georgius Papánek, but Valentini’s work – similarly to authors of all other nationalities of that time in the Kingdom of Hungary – of course contains mythical and legendary elements, to which he naturally utilizes the reports of antique Greek and Roman writers about Eastern-origin exotic peoples. The Nagykároly (Carei, Szatmár county)-based Ferdinandus Thomas, for example, derives the origin of Hungarians from Ethiops! But we can name examples from either Romanian or South Slav literatures. Valentini is of high significance, because in many ways he – with his poet colleagues, writing in Slovak or other language – clears the way for Orientalism, an important trend of European Romanticism.